2001
DOI: 10.1002/ijc.10351
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting histologic evidence of prostatitis is unrelated to postimplant urinary morbidity

Abstract: Fax: (206)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…However, one study has indicated that no correlation exists between preoperative prostatitis and postoperative urinary morbidity (Hughes, Wallner, Merrick, Miller, & True, 2001).…”
Section: Patient Factors Preexisting Urinary Symptomsmentioning
confidence: 99%
“…However, one study has indicated that no correlation exists between preoperative prostatitis and postoperative urinary morbidity (Hughes, Wallner, Merrick, Miller, & True, 2001).…”
Section: Patient Factors Preexisting Urinary Symptomsmentioning
confidence: 99%
“…Гипофракционирование [215,216]. Проведенные исследования показали также, что наличие простатита не влияет на качество мочеиспускания после проведения имплантации [217], а воспалительные заболевания кишечника не приводят к увеличению гастроинтестинальной токсичности [219]. Возраст пациента также не является лимитирующим фактором при проведении БТ: переносимость процедуры практически сравнима для разных возрастных групп, а хорошие результаты безрецидивной выживаемости среди более молодых пациентов расширяют возможности применения методики [220].…”
Section: ограничения по дозам облучения на критические органы [203 204]unclassified